COMMUNITY STRUCTURE OF MANGROVE VEGETATION IN MENGKAPAN VILLAGE SUNGAI APIT DISTRICT OF SIAK - Fia Novianty; Aras Mulyadi; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted in January-February 2017 in Mengkapan Village, Sungai Apit, District of Siak. The purpose of study was to determine the structure community of mangrove in Mengkapan Village. The method used in the research was survey method. The stations were determined based on human activity. Each station was determined in three transects set along 100 m from the sea toward the land. The number of plots was 27, with the size of 10 x 10 m2 for tree criteria, 5 x 5m2 for sapling criteria, and 2 x 2m2 for the seedlings criteria. The results of this study found 10 species of mangrove. The vegetation was dominated by species of R. apiculata with value 155.71%. The status of mangrove vegetation in Mengkapan Village, Sungai Apit was in bad condition, with the average density of 607.40 ind/ha.Keywords: Mangrove, Structure community, Village Mengkapan